2018
DOI: 10.18178/ijlt.4.2.107-113
|View full text |Cite
|
Sign up to set email alerts
|

Facebook and Collaborative Learning: An Empirical Study on Online Assessment

Abstract:  Abstract-Collaborative learning induces participation and involvement amongst learner. However, the distribution of tasks within a collaborative environment may lead to unequal contributions of shared roles and responsibilities due to the common perils in the case of social loafing or domineering learners. Current trends in the area of collaborative learning have established an array of approaches designed to constitute a sense of accountability and relations of constructive interdependence amongst learners.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…They concluded that the incorporation of online peer assessment and collaborative learning environment enhance students' interest and motivation. The findings of the previous study conducted by Mahmud and Wong (2018) also acknowledged the findings of the present research which found that the use of collaborative writing on Facebook encouraged students' motivation, attitude, and attention in writing recount text.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…They concluded that the incorporation of online peer assessment and collaborative learning environment enhance students' interest and motivation. The findings of the previous study conducted by Mahmud and Wong (2018) also acknowledged the findings of the present research which found that the use of collaborative writing on Facebook encouraged students' motivation, attitude, and attention in writing recount text.…”
Section: Discussionsupporting
confidence: 86%
“…However, the previous study conducted by Mahmud and Wong (2018) did not investigate the teacher's ways in improving the students' ability in writing recount text through collaborative writing on Facebook. Furthermore, Mahmud and Wong (2018) focused on peer assessment's integration for an English Critical and Creative Writing class.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations